Fire scenario influence on the fire resistance and the behavior of RC frame structure - Cvetkovska, Meri; Chifliganec, Cvetanka; Trombeva Gavriloska, Ana; Lazarevska, Marijana; Mircevska, Violeta (University of Novi Sad, Faculty of Technical Sciences; Higher Education Technical School of Professional Studies, 2017)
Understanding the performance and the response of the frame structures in fire is of particular importance for structural fire design. The specialized computer program SAFIR enables analysis of different types of structures, constructed with different structural materials. The options of program SAFIR are presented on eight different fire scenarios of standards fire exposure of three bay two story RC frame. The results for the: temperature distribution within the structural elements, fire resistance of the whole structure, bending moments and deformations of elements are presented and discussed. The worst fire scenario of the frame is defined.
Keywords: reinforced concrete frame, fire resistance, fire scenario, internal forces, deformation